Organizational diagnosis of the Family Poultry Cooperative of the Alagoas Sertão (COOPAFAS) of Santana do Ipanema - AL / Diagnóstico organizacional da Cooperativa de Avicultores Familiares do Sertão Alagoano (COOPAFAS) de Santana do Ipanema - AL - Alex Romualdo Nunes de Oliveira; Conceição Maria Dias de Lima; Cristina França Soares; Patrícia Tavares Melo; Páblio Rickel Moraes da Silva; Agenor Farias Neto (Universidade Estadual de Alagoas, 2017)
The research had as objective to observe the aspects related to the development of the cooperative, aspects that are inserted in the report in compliance with the requirements of the Cooperativism discipline. The justification of the work is given by the relevance of studying and understanding aspects of the organization of COOPAFAS and its impacts to the place. The methodology used was the study of a case, using interview with semi-structured script and observation. During the survey, information was obtained on the fundraising by the cooperative for its constitution, being established with a part of R $ 1,200.00 per cooperative, divided into 34 plots. There were 100 cooperative members at the outset, and today it has 93 members. The main difficulties faced by the cooperative are the need to run the municipal poultry slaughterhouse with at least the state inspection seal and improvement of the cold chamber capacity which currently supports 3,500 kg (on average 1,500 birds). In relation to the environmental impacts provoked, the positive point is that because it is an activity that demands small areas to work, it does not have to carry out deforestation like other activities. The negative point is the slaughtering of birds, which is done in a slaughterhouse that is not owned by the cooperative, which lacks control over the disposal of the waste. The field visit to the poultry and farmers' cooperative in Backwoods Alagoano was very useful, because we can have contact with how a cooperative works, and know the challenges to be faced in order to improve its operation.